2023
DOI: 10.3390/jfb14080412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biocompatibility of PLA/PHB/TPS Polymer Scaffolds with Different Additives of ATBC and OLA Plasticizers

Marianna Trebuňová,
Patrícia Petroušková,
Alena Findrik Balogová
et al.

Abstract: One of the blends that is usable for 3D printing while not being toxic to cell cultures is the lactic acid (PLA)/polyhydroxybutyrate (PHB)/thermoplastic starch (TPS) blend. The addition of plasticizers can change the rate of biodegradation and the biological behavior of the material. In order to evaluate the potential of the PLA/PHB/TPS material in combination with additives (plasticizers: acetyl tributyl citrate (ATBC) and oligomeric lactic acid (OLA)), for use in the field of biomedical tissue engineering, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Table 4 summarizes studies that use different methods to obtain scaffolds with PHB for BTE. 7,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] Similarly, a compilation of different investigations was carried out where the geometry (Table 5) and manufacturing technique (Figure 3) of the PHB scaffolds were compared for skin, nerve, cartilage, and bone applications.…”
Section: Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Table 4 summarizes studies that use different methods to obtain scaffolds with PHB for BTE. 7,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] Similarly, a compilation of different investigations was carried out where the geometry (Table 5) and manufacturing technique (Figure 3) of the PHB scaffolds were compared for skin, nerve, cartilage, and bone applications.…”
Section: Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Trebu ňová et al tested the composite material PLA/PHB for cultivation and cytotoxicity while evaluating the most optimal ratio of individual components for the mentioned parameters. They observed that the composite material did not show any significant signs of cytotoxicity [152].…”
Section: Biocompatible Synthetic Scaffoldmentioning
confidence: 99%
“…Starch can be used as nanofillers in the form of starch nanocrystals, preserving its native crystalline form or as a matrix, in the form of thermoplastic matrix when processed with water and/or plasticizer, destructuring its granules [ 15 ]. In the recent years, blends of PLA and thermoplastic starch (TPS) have been studied as environmentally friendly materials of great interest for food packaging and biomedical applications [ 16 , 17 , 18 ]. However, the major drawback of processing PLA blends through simple physical blending is their immiscibility, poor compatibility, and the weak interfacial bonding of the blend components [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%